The concentric dynamic of the ‘Shanghai cooperation’ for Iran and the issue of ‘Pan-Asia-centrism’ (Халықаралық қатынастар және халықаралық құқық сериясы, 2020)
This article is devoted to the study of the conceptual relationship between the concepts of “regionalaxis” between neighboring states and the concept of “Pan-Asia-centrism”. On the example of Iran’sforeign policy, these concepts and the possibilities of its foreign policy choice are considered taking intoaccount the activities of regional groups. Two approaches to understanding the concept of "Pan-Asiacentrism"are considered. Based on the approach of prof. J. Ibrashev to the understanding of “Pan-Asiacentrism”,the article analyzes three dimensions of the SCO, three concentric circles around the SCO.The first circle includes the closest dimension, neighbors on a territorial basis. The second circle involvesexploring an expanded understanding of "neighbors." The third circle is an intercontinental dimension.In Western political thought, reasoning is often held in terms of alienation or isolation. This is not suitablefor understanding the dynamics of the development of non-Western countries in the 21st century.Around Central Asia, a broad forum is being formed with a concentric inclusion of the countries of EastAsia, West Asia, and South Asia. This is a very important trend after the end of the Cold War. The articlemakes an attempt to consider a hypothetical analysis of the consequences of the development of this trend,to offer a number of possible scenarios and understand what the trend of the SCO expansion is.Key words: International System, Foreign Policy of Iran, Neighbourhood policy, New regionalism,Merging of diplomatic interests, “Co-sovereignisation”.